11(9c-1)-4=97c+11

Simple and best practice solution for 11(9c-1)-4=97c+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(9c-1)-4=97c+11 equation:


Simplifying
11(9c + -1) + -4 = 97c + 11

Reorder the terms:
11(-1 + 9c) + -4 = 97c + 11
(-1 * 11 + 9c * 11) + -4 = 97c + 11
(-11 + 99c) + -4 = 97c + 11

Reorder the terms:
-11 + -4 + 99c = 97c + 11

Combine like terms: -11 + -4 = -15
-15 + 99c = 97c + 11

Reorder the terms:
-15 + 99c = 11 + 97c

Solving
-15 + 99c = 11 + 97c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-97c' to each side of the equation.
-15 + 99c + -97c = 11 + 97c + -97c

Combine like terms: 99c + -97c = 2c
-15 + 2c = 11 + 97c + -97c

Combine like terms: 97c + -97c = 0
-15 + 2c = 11 + 0
-15 + 2c = 11

Add '15' to each side of the equation.
-15 + 15 + 2c = 11 + 15

Combine like terms: -15 + 15 = 0
0 + 2c = 11 + 15
2c = 11 + 15

Combine like terms: 11 + 15 = 26
2c = 26

Divide each side by '2'.
c = 13

Simplifying
c = 13

See similar equations:

| 5*0.166666666=a | | 8-21=75 | | 8(3+y)=4x-y | | 5+3=22 | | N-3=11+3 | | -8(7-3y)=-18 | | 12=5-8m | | 6b^2+35b+36=0 | | 3x=-y+4500 | | -6(4x+7)+x= | | 2(5x+3)+3x= | | 3x-y+33=0 | | 4.6r-3.2=3.2r-3.9 | | M^0n^6=0 | | 3x+100=-5x+900 | | 7x+28=70 | | 7x+14=2x+18 | | 14-18=40 | | 54+18x= | | 5.6+2.5=.9r | | 4+10=72 | | 16=-16t^2+16t+32 | | -15n+17=-14n-2 | | 7.8=23.4 | | 5(9.5-8h)=-20.5 | | 18-22=120 | | 4-11=120 | | 20a^2-15a= | | 3k+4+6k=-8+8k | | 3-8=35 | | m-4=22 | | 5+5+5=3x |

Equations solver categories